Christianity and natural law : an introduction / edited by Norman Doe, Cardiff University - Doe, Norman (Law and Christianity., 2017)
Historically, natural law has played a pivotal role in Christian approaches to the law, and a contested role in legal philosophy generally. However, comparative study of natural law across global Christian traditions is largely neglected. This book provides not only the history of natural law ideas across mainstream Christian traditions worldwide, but also an ecumenical comparison of the contemporary natural law positions of different traditions. Its focus is not solely theoretical: it tests the practical utility of natural law by exploring its use in the legal systems of the churches studied. Alongside analysis of the assumptions underlying the concept, it also proposes a jurisprudence of Christian law itself. With chapters written by distinguished lawyers and theologians across the world, this book is designed for those studying and teaching law or theology, those who practice and study ecumenism, and those involved in the practice of church law.